Correction: Barak, S. et al. “Long-Term Outcomes of Early Enzyme Replacement Therapy for Mucopolysaccharidosis IV: Clinical Case Studies of Two Siblings”. Diagnostics 2020, 10, 108 - Sharon Barak; Yair Anikster; Ifat Sarouk; Eve Stern; Etzyona Eisenstein; Tamar Yissar; Nir Sherr-Lurie; Annick Raas-Rothschild; Dafna Guttman (Diagnostics, 2020)
The authors wish to make the following correction to this paper [...]